Catastrophic health expenditures incurred by families in 2003, 2009 and 2018 in the Federal District, Brazil: evolution and composition - Pedro Henrique Alves Santos; Theo da Fonseca Torres; Letícia Xander Russo; Everton Nunes da Silva (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To investigate the evolution of prevalence of catastrophic health expenditure in the Brazilian Federal District at three different times (2003, 2009 and 2018), as well, to identify the composition of outof- pocket expenditure in the respective years. Method Time series study, using descriptive data from the Family Budget Survey. Prevalence was stratified by consumption quintiles. Results 754 households were selected as a sample in 2003, 695 in 2009 and 1,000 in 2018. Taking a 10% consumption threshold, prevalence of catastrophic expenditure was 12.3% (95%CI 9.6;14.9) in 2003, 15.3% (95%CI 12.1;18.3) in 2009 and 14.1% (95CI% 11.8;16.2) in 2018. Households with lower income had higher prevalence of catastrophic expenditure. Medicines have a greater burden on expenditure of low-income families. Conclusions There was an increase in prevalence of catastrophic expenditure in the Federal District. Medicines were the main expense for the poorest families.